Sitting Behaviors and Mental Health among Workers and Nonworkers: The Role of Weight Status - Karin I. Proper; H. Susan J. Picavet; Wanda J. E. Bemelmans; W. M. Monique Verschuren; G. C. Wanda Wendel-Vos (Hindawi Limited, 2012)
Objective. To explore the associations between sitting time in various domains and mental health for workers and nonworkers and the role of weight status. Design. Cross-sectional analyses were performed for 1064 respondents (47% men, mean age 59 years) from the Doetinchem Cohort Study 2008-2009. Sedentary behavior was measured by self-reported time spent sitting during transport, leisure time, and at work. Mental health was assessed by the Mental Health Inventory (MHI-5). BMI was calculated based on measured body height and weight. Results. Neither sitting time during transport nor at work was associated with mental health. In the working population, sitting during leisure time, and particularly TV viewing, was associated with poorer mental health. BMI was an effect modifier in this association with significant positive associations for healthy-weight non-workers and obese workers. Conclusion. Both BMI and working status were effect modifiers in the relation between TV viewing and mental health. More longitudinal research is needed to confirm the results and to gain insight into the causality and the underlying mechanisms for the complex relationships among sedentary behaviors, BMI, working status, and mental health.